Drug-induced toxicodermia as implication of a drug disease - O. L. Romanova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Toxicodermia belongs to the widespread and serious types of adverse reactions to medicines, affects doctors of all specialties and medical institutions of any profile. The risk of development of a toxicodermia for the majority of medicinal preparations makes 20% of all medicinal complications.